Lung Volume Change After Pedicle Subtraction Osteotomy in Patients With Ankylosing Spondylitis With Thoracolumbar Kyphosis. Issue 4 (15th February 2015) - Zhang, Guoying; Fu, Jun; Zhang, Yonggang; Zhang, Wei; Zhang, Xuesong; Wang, Zheng; Mao, Keya; Wang, Yan
<x xml:space="preserve">Abstract</x> Study Design. A retrospective clinical study. Objective. To investigate the lung volume (LV) change in patients with ankylosing spondylitis (AS) with thoracolumbar kyphosis after the pedicle subtraction osteotomy procedure. Summary of Background Data. Thoracolumbar kyphosis with respiratory impairment is the consequence of most untreated AS patients. Restrictive pulmonary function is prevalent in these patients. The ideal evidence for restrictive pulmonary function impairment is to investigate the LV. A computed tomography (CT)-based method can help to obtain accurate LV change during the osteotomy. Method. Twenty-eight patients with AS with thoracolumbar kyphosis were included. All of these patients underwent pedicle subtraction osteotomy to correct their sagittal deformity. Pre- and postoperative full-length radiographs and CT scans were reviewed. The sagittal correction of the spine was measured. CT scans were used to estimate the pre- and postoperative LV with software. The relationship between the sagittal correction and the LV change was investigated. All the patients were followed up for 2 years at least. Results. The pedicle subtraction osteotomy procedure was performed safely on each patient without serious complications. The average preoperative T1–S1 Cobb was 67.7° (42° ∼ 88°) and the postoperative was 7.6° (−11° ∼ 21°). T1–S1 Cobb change was 60.0° in average (P < 0.05). The LV increased by 396 mL in average. Significant correlation was found between the percentage of LV change and T1–S1 Cobb change (r = 0.7219, P < 0.05). The location we selected for pedicle subtraction osteotomy varied from T12 to L3. No relationship was found between the osteotomy location and the LV change. Conclusion. The pedicle subtraction osteotomy effectively corrected the sagittal deformity of patients with AS. LV increased significantly after the osteotomy. Level of Evidence: 4